Hydrophilic interaction chromatography in food matrices analysis: An updated review. (15th August 2018) - Marrubini, Giorgio; Appelblad, Patrik; Maietta, Mariarosa; Papetti, Adele
Highlights: Analysis of food components using hydrophilic interaction chromatography is reviewed. Advantages/disadvantages of HILIC in vegetable and animal food analysis is discussed. The reviewed HILIC methods focus on the papers from 2011 to submission date in 2017. Abstract: This review focuses on the most recent papers (from 2011 to submission date in 2017) dealing with the analysis of different organic components in foods (i.e. nucleobases, nucleosides, nucleotides, uric acid, and creatinine, amino acids and related compounds, choline-related compounds and phospholipids, carbohydrates, artificial sweeteners and polyphenolic compounds), using hydrophilic interaction liquid chromatography (HILIC) combined with different detection techniques. For each compound class, the investigated food matrices are grouped per: foods of animal origin, vegetables, fruits and related products, baby food, and other matrices such as drinks and mushrooms/fungi. Furthermore, the main advantages of HILIC chromatography respect to the other commonly used techniques are discussed.